Blair et al. Humpback foraging dives - Blair, Hannah B.; Merchant, Nathan D.; Friedlaender, Ari S.; Wiley, David N.; Parks, Susan E. (Dryad Digital Repository, 2016)
Spreadsheet with metadata and measurements for all foraging dives analyzed. This includes the tag record ID, individual, year and month collected, total dive time, descent rate, ascent rate, maximum dive depth, number of bottom side-rolls, time between foraging dives, surface time immediately following dive, whether or not ship noise was present during the dive, and received level of noise during the dive.